Compensation for Breach in Community-Based Mountain Open Trips: Ganti Rugi Atas Pelanggaran dalam Perjalanan Terbuka Berbasis Komunitas di Pegunungan - Taufany, Firdaus Enov At; Purwaningsih, Sri Budi (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Open trip mountain services organized by communities are increasingly popular but prone to breaches of contract, causing losses to climbers. Specific Background: Cases such as forced descent at Pos 2 Sembalun Lawang, Gunung Rinjani, highlight the lack of clarity regarding compensation rights in community-managed trips. Knowledge Gap: Existing literature rarely addresses the intersection of civil law principles and economic transaction theories in regulating compensation for open trip services. Aim: This study analyzes legal obligations and compensation mechanisms for climbers affected by breaches of contract using civil law perspectives and supply-and-demand theory. Methods: Normative legal research with statutory and economic theory approaches, supplemented by secondary sources, analyzed descriptively. Results: Participants are entitled to compensation when services fail to meet agreed standards. Theories of offer, acceptance, and trust clarify when agreements are legally binding and how liability arises. Dispute resolution can occur through mediation, arbitration, or court litigation, with distinct procedural considerations. Novelty: Integrating legal theory with economic principles provides a clearer framework for determining compensation and managing expectations in open trip services. Implications: Understanding these frameworks enhances legal certainty and protects climbers’ rights in community-organized outdoor tourism. Highlights: Legal responsibility arises upon confirmation of trip participation. Theories of offer, acceptance, and trust guide compensation claims. Multi-path dispute resolution supports fair and efficient outcomes. Keywords: Compensation, Breach of Contract, Open Trip, Civil Law, Community Tourism